STUDENTS’ BELIEF ON USING CERTAIN LEARNING STRATEGIES IN IMPROVING THEIR SPEAKING ABILITY - Kurniati, Endang; Cahyono, Bambang Yudi (PEOPLE: International Journal of Social Sciences, 2018)
Students have their own belief in using certain Language Learning Strategies (LLSs) including the students in a private institute in Indonesia. The previous research revealed that beliefs affects the formulation of effective teaching methods and will carry out the improvement of learners’ language learning abilities. In addition, some scholars identified that LLSs are differed by some factors. It was found that females tend to use cognitive strategies and males use metacognitive strategies. Other research by Šafranj, J. (2013) supported the previous research finding that sex differences in strategy use had a profound influence. This paper investigates the students’ belief on using certain Learning Strategies supporting their speaking ability and to find out the possible unrevealed learning strategies. There were 33 students of a private institute in Indonesia being included in this research. The finding shows that the students have strong belief that three learning strategies support much on their speaking improvement: MS (Memory Strategies), AS (Affective Strategies), and SS (Social Strategies). The following researchers are expected to cover students' belief associated with the other skills especially that of receptive one.